Okoliczności powstania oraz przejawy działalności religijnej i kulturowej jezuitów w Płocku w XVII i XVIII wieku - Graczyk, Waldemar (Biuletyn Historii Wychowania, 2014)
The goal of this article is to present the circumstances accompanying the establishment of the Jesuit collegium in Płock. The author analyses the economic, political and cultural bases of the foundation as well as the role played in this venture by bishops Andrzej Noskowski and Marcin Szyszkowski. Finally, in 1616 the Jesuit foundation in Płock was approved by the Polish Parliament. The article includes a description of the working methods employed by the Jesuit teachers, the curricula, as well as the extra-curricular forms of affecting the local community of the Jesuit Society Collegium – the Sodality of Our Lady and other organized and informal religious societies. What is more, the Jesuits working in Płock were involved in propagating the Catholic faith. The author also discusses the importance of the school theatre in introducing the models of raising children promoted by Jesuits.